2021
DOI: 10.1002/jnm.2925
|View full text |Cite
|
Sign up to set email alerts
|

A review on methods to simulate three dimensional rotating electrical machine in magnetic vector potential formulation using edge finite element method under sliding surface principle

Abstract: In recent years edge finite element method has become quite popular in modeling the three-dimensional rotating electrical machine due to its ability to represent the physical behavior of field along interface correctly. However, modeling becomes complex when significant mesh distortion occurs along a sliding surface due to movement. A remeshing step is needed, which increases computational cost. In order to avoid remeshing, efficient numerical methods have already been developed to model movement in the three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As  T acts only with respect to time, the properties ( 5), (7) of Section 3 remain valid. For completeness, we prove the following lemma.…”
Section: Equal Trial and Test Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…As  T acts only with respect to time, the properties ( 5), (7) of Section 3 remain valid. For completeness, we prove the following lemma.…”
Section: Equal Trial and Test Spacesmentioning
confidence: 99%
“…Application of this technique in the static case is investigated in [34]. Extensive studies of the static case can be found not only for analytic methods, but also for the approximation by finite elements, see for example, [7], or in a more applied static nonlinear example [19]. Moreover, the quasi‐static case is examined, see [6].…”
Section: Introductionmentioning
confidence: 99%